Effect of bioagents on spore germination of Erysiphe polygoni - Pipliwal, Sunil Kumar; Jadeja, K B; Sharma, Anshul; Dhakad, Jitendra (Indian Journal of Plant Protection, 2020)
The study on the effect of bioagents on spore germinaton of Erysiphe polygoni was conducted at Department of Plant Pathology, College of Agriculture, Junagadh Agricultural University, Junagadh, Gujarat in year 2012-13. The antifungal properties of cultural filtrate of Trichoderma isolates proved effective against the spore germination of Erysiphe polygoni. Minimum spore germination was observed with the cultural filtrate of Trichoderma isolate-5 followed by Trichoderma isolate-14. In case of cultural filtrate of Pseudomonas fluorescens isolates, Minimum spore germination was observed with the cultural filtrate of P. fluorescens isolate-7 followed by P. fluorescens isolate-4.